Лексико-семантические особенности французского театрального дискурса в драматургическом театре конца XIX века и в театре абсурда начала XX века - Ищенко, В.И. (Культура народов Причерноморья, 2014)
В статье рассмотрены особенности французского театрального дискурса как вида
частного дискурса. Автор предлагает сосредоточить внимание на определениях театральный дискурс,
театральная семиотика, театральный текст и осуществляет анализ нескольких французских
произведений. На основе проведенного исследования введены в научный оборот и обоснованы понятия
«театральный текст», как минимальная семиотическая единица театрального текста, «театральный
маркетинг». У статті розглянуті особливості французького театрального дискурсу як виду приватного
дискурсу. Автор пропонує звернути увагу на визначення театрального дискурсу, театральної
семіотики, театральний текст та здійснює аналіз кількох французьких творів. На основі проведеного
дослідження введені і обґрунтовані поняття «театральний текст», як мінімальна семіотична одиниця
театрального тексту, «театральний маркетинг». The article examines the theatrical French discourse as a kind of private discourse. The author
proposes to focus attention on the concept of theatrical discourse, theater semiotics, theatrical text, and analyzes
several French works. The theatrical discourse refers sign-oriented and symbolic activities carried out in the
public communication space and exhibit required properties: entirety, logicality, informative, communicative
and pragmatic trend. Theatrical semiotics is a method of analyzing the text or representations, revealing their
formal structure, considering the dynamics of the process of forming and becoming signs of what is happening
with the participation of the public and the creators of the performance. Theatrical text - is a message containing
dramatic work’s information in a certain genre of theater. On the basis of the conducted research it was
introduced into science and substantiated the concept of «theater text» as the minimum unit of semiotic
theatrical text, a «theatrical marketing».